(3GdahGFO GdafGQjI Ydi GdQSGdI GdCKjQIs - (3GdafGQj (B( (3GdaQfj (B)(3, GdQhej, TeS GdOjf, eMeO Hf MeRI Hf eMeO, J (B834 (3g`s ((3eMeO Hf SdjeGfs)
(3ChdgG (B:s
(3HYO GdHSedI ; MeOG dc Gddge Ydi eG dNUJ dj ef efM YhGQa GdCaGVd CeG HYO Cf CcJH ahGjO dGFbI HeWGdYI GdENhGf dahGjO GdQSGdI GdCKjQjI aj GdejRGf TQYJ aj ZOhI jhe ef CbUQ GdCjGe hNJeJ eY CPGfg eZQHg HYhf Gddg Gdedc GdYdGe s
(3BNQgG (B:s
(3aGdeWGdYI efMUQI aj GdbSejf GdSaSWI hGdeTGZHI hGdYeOI Cj GdeYJeO Ydjg gh GdHQgGf dG ZjQ dCf JMUjd GdYbGjO GdMbI hJRjd GdYbO GdHGWdI djS EdG Hgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 110s
(3eYLe GdeDdajf (B3 / 269s
(3cTa GdXfhf (B1 / 207s
(3TPQGJ GdPgH (B7 / 209s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs